DEVELOPING LOCAL CULTURE-BASED FABLES FOR TEACHING ENGLISH FOR YOUNG LEARNERS - -, Tri Mulyati; Khusnul Khotimah; Wiwin Indiarti (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
One of the most important aspects in the teaching and learning process is the material use. Therefore, the teachers must prepare the materials in such away that those will be interesting and not monotonous for students. The aim of this research is to develop fable reading materials based on local Banyuwangi culture for young learners at MI Nurul Karim Bangsring. This research follows the research procedure proposed by Sugiyono. The development stages covered potential and problems, designing, small group trial, and revision. The results of the research and development show that the product reaches very feasible level based on English teacher validation and students’ validation. Therefore, it can be concluded that fable reading materials based on local Banyuwangi culture can be used in teaching and learning activities in English language learning in class V at MI Nurul Karim Bangsring.